Ambulatory Care Sensitive Admissions in Individuals With Autism Spectrum Disorder, Intellectual Disability, and Population Controls. Issue 2 (14th December 2018) - Hand, Brittany N.; Boan, Andrea D.; Bradley, Catherine C.; Charles, Jane M.; Carpenter, Laura Arnstein
Abstract : Ambulatory care sensitive (ACS) admissions are those for which effective primary care can prevent the need for emergency department (ED) visits and inpatient hospitalizations, and are an indicator of primary care access. Individuals with autism spectrum disorder (ASD) and/or intellectual disability (ID) may be at higher risk for ACS admissions than individuals in the general population due to difficulty accessing primary care. The objective of this study was to compare the incidence of ACS admissions among four cohorts of individuals aged 2–24 years: ASD without co‐occurring ID (ASD‐only), ASD with co‐occurring ID (ASD + ID), ID without ASD (ID‐only), and population controls (PC). Data from ED visits and inpatient hospitalizations occurring between January 1, 2000 and December 31, 2015 were examined to identify ACS admissions. Generalized linear models were used to examine differences between cohorts on the number of ACS ED visits and inpatient hospitalizations. Results revealed the ASD + ID and ID‐only cohorts had significantly higher rates of ACS inpatient hospitalizations than the PC cohort. Additionally, the ID‐only cohort had higher rates of ACS ED visits than the PC cohort. The ASD‐only and PC cohorts did not differ on incidence of ACS admissions. These findings suggest that presence of an ID with or without co‐occurring ASD increased the risk for ACS inpatient hospitalizations, and presence of ID‐only increased the risk for ACS ED visits. Future work should examine trajectories of ACS admissions over time and consider inclusion of additional characteristics that may elucidate reasons for differences in ACS admissions among these groups. Autism Res 2019, 12: 295–302 © 2018 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Preventable hospitalizations are a common indicator of problems with access to quality primary healthcare. Findings of this study suggest that individuals with intellectual disability, with or without autism spectrum disorder, have higher rates of preventable hospitalizations than the general population. Further research is needed to understand how to improve access to primary care and reduce preventable hospitalizations for this vulnerable population.